2020
DOI: 10.1111/acel.13151
|View full text |Cite
|
Sign up to set email alerts
|

TORC1 signaling regulates cytoplasmic pH through Sir2 in yeast

Abstract: Glucose controls the phosphorylation of silent information regulator 2 (Sir2), a NAD+‐dependent protein deacetylase, which regulates the expression of the ATP‐dependent proton pump Pma1 and replicative lifespan (RLS) in yeast. TORC1 signaling, which is a central regulator of cell growth and lifespan, is regulated by glucose as well as nitrogen sources. In this study, we demonstrate that TORC1 signaling controls Sir2 phosphorylation through casein kinase 2 (CK2) to regulate PMA1 expression and cytoplasmic pH (p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 77 publications
(129 reference statements)
0
7
0
Order By: Relevance
“…The TOR signaling pathway is a central regulator that connects nutrient availability and stress condition to control cell growth and lifespan. Inhibition of the TORC1 signaling pathway delays aging and extends lifespan by manipulating the activities of downstream kinase proteins, transcription factors and NAD + -dependent deacetylase enzyme Sir2 in Saccharomyces cerevisiae [ 5 , 6 , 12 ]. Inhibition of TORC1 signaling reduces expression of ribosomal protein genes such as RPS26A and RPL9A, indicating downregulation of protein synthesis and upregulation of the anti-aging process [ 12 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The TOR signaling pathway is a central regulator that connects nutrient availability and stress condition to control cell growth and lifespan. Inhibition of the TORC1 signaling pathway delays aging and extends lifespan by manipulating the activities of downstream kinase proteins, transcription factors and NAD + -dependent deacetylase enzyme Sir2 in Saccharomyces cerevisiae [ 5 , 6 , 12 ]. Inhibition of TORC1 signaling reduces expression of ribosomal protein genes such as RPS26A and RPL9A, indicating downregulation of protein synthesis and upregulation of the anti-aging process [ 12 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The target of rapamycin (TOR) is a nutrient-sensing protein kinase which is evolutionarily conserved in eukaryotic organisms [ 4 ]. Evidence indicates that the TOR signaling pathway is a central regulator that connects nutrient availability and stress condition to control cell growth and lifespan [ 4 , 5 , 6 ]. The inhibition of the TORC1 signaling pathway can delay aging and extend the lifespan of different species such as Saccharomyces cerevisiae , Caenorhabditis elegans , Drosophila melanogaster and mice [ 6 , 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Early studies revealed the Sirtuins and TOR (Target of Rapamycin) signaling as longevity regulators (Longo and Kennedy 2006 ; Powers et al 2006 ; Wierman and Smith 2014 ). These proteins (the Sirtuins and TOR factors) provide insight on and have revolutionized aging biology (Deprez et al 2018 ; Devare et al 2020 ). Besides playing a key role in identifying over 1000 genes through the CLS paradigm in S. cerevisiae (Jung et al 2015 ), genetic techniques have revealed several pathways and regulatory networks that intersect to modulate lifespan.…”
Section: Introductionmentioning
confidence: 99%